(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we introduce the notions of strong â€ âˆ§ â€-hyperlattices, hyperideals and hyperfilters in strong â€âˆ§â€-hyperlattices. Also, we give equivalence conditions for prime hyperfilters (hyperideal) in strong âˆ§-hyperlattices. Distributivity (dual distributivity) in â€âˆ§â€-hyperlattices,IA-hyperideals and prime hyperfilters in strong â€ âˆ§ â€-hyperlattices are investigated.